1998
DOI: 10.1002/(sici)1098-0997(1998)6:1<38::aid-idog8>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of famciclovir in the management of genital herpes

Abstract: The frequent occurrence of genital herpes continues to be a serious clinical problem. Although not life threatening, the physical symptoms of the disease, and the ensuing psychosocial complications, can be overwhelming to patients. The life cycle of the herpes simplex virus is complex, comprising multiple stages. Following infection, the virus establishes life‐long latency in its host and can reactivate at any time as a recurrent infection. Successful management of genital herpes simplex infections involves pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…•Famciclovir , 250 mg t.d.s. for 7–10 days, is the prodrug of penciclovir, a new agent which also has a higher bioavailability than acyclovir and has been shown to be effective in suppressing recurrent genital herpes (18).…”
Section: Genital Herpesmentioning
confidence: 99%
“…•Famciclovir , 250 mg t.d.s. for 7–10 days, is the prodrug of penciclovir, a new agent which also has a higher bioavailability than acyclovir and has been shown to be effective in suppressing recurrent genital herpes (18).…”
Section: Genital Herpesmentioning
confidence: 99%
“…272 Famciclovir is an alternative treatment option for genital herpes. 273,274 As substantiated by research findings, zinc has demonstrated the capacity to impede the viral life cycle of HSV. 275 Furthermore, an investigator study has highlighted the potential benefits of synergising eucalyptol and acyclovir in addressing resistant HSV infections.…”
Section: Current Antiviral Therapies For Hsv Infectionmentioning
confidence: 97%
“…Efforts to address these challenges include developing innovative therapies targeting acyclovir‐resistant herpes simplex keratitis 272 . Famciclovir is an alternative treatment option for genital herpes 273,274 . As substantiated by research findings, zinc has demonstrated the capacity to impede the viral life cycle of HSV 275 .…”
Section: Therapeutic Approaches and Future Directionsmentioning
confidence: 99%
“…Its mechanism of action is through penciclovir; penciclovir triphosphate inhibits herpes DNA synthesis by acting as a substrate for viral DNA polymerase. The major clinical indications for famciclovir use are treatment of herpes zoster, recurrent genital herpes, 52 and recurrent herpes labialis. 53 Famciclovir can also be used as suppression therapy to reduce the risk of recurrent genital herpes as well as oral treatment of uncomplicated varicella in HIV-infected patients.…”
Section: Antiherpes Drugsmentioning
confidence: 99%